Verification of the chromosome number using cytogenetics and estimation of genome size via flow cytometry and k-mer analyses for representative Anoectochilus roxburghii accessions - Wenting Zhang; Yu Mei; Jihua Wang (PLoS ONE, 2025)
Anoectochilus roxburghii (Wall.) Lindl. is a perennial herb of orchidaceae. Because of its functions of heat-clearing and blood-cooling, removing dampness, detoxification and enhancing immunity, it is considered as a nutritious medicinal plant with high economic value. Originating from Guangdong province, China, chromosome number and genome size of A. roxburghii (“Luofushan-1”) were determined through cytogenetics, flow cytometry, and k-mer analysis. We analyzed the karyotype of A. roxburghii using different cytogenetic markers, and the results showed a chromosome number of 2n = 80, but no sex-linked chromosome heterotropy was observed. For flow cytometry analysis, tomato and maize were used as internal standard, and the 2C DNA amount among sixteen Anoectochilus accessions ranged from 6.57 to 8.26 pg (including Luofushan-1). Additionally, a genome survey of “Luofushan-1” was performed using Illumina HiSeq 2000 DNA sequencing, k-mer analysis revealed that the genome size of “Luofushan-1” was approximately 5.68 Gbp. This comprehensive study establishes a foundation for subsequent whole-genome sequencing of A. roxburghii, contributing valuable insights into its genetic characteristics and paving the way for further research on this medicinal plant.